Smart information board based on PSOC 6 MCU - Lozynskyi, Yurii; Torubka, Taras (Видавництво Львівської політехніки, 2022)
Nowadays, the development of electronics and related technologies is very fast. An extremely significant role in the life of moder society is took by information output devices, the development and modernization of which is an urgent task. Using the idea regarding wireless control of remote devices, an information board with remote control was developed. This article provides a reader with the development of universal information board which customers will be able to assemble for the dimensions that they need. The created device displays text news from websites, displays time and important messages. For the convenience of updating information and automation – the board should have WiFi with Internet connection. The information board is a great way to receive news quickly, without using other means to obtain information. The information board is designed on the CY8C624ABZI-D44 microcontroller. Also, important structural elements of this board are: buffer chip – SN74ALS244CN, LED matrix control chip – MAX7219, LED matrix – 1088AS and WiFi module – LBEE5KL1DX. The functional diagram of the module 1088AS and MAX7219 connected to PSoC 6 has been designed.
Keywords: server; HTML; client; XML file; WiFi; PSoC 6; microcontroller; display; data; MCU ARM; Quad SPI; NOR Flesh Memory; NT. RTOS